Increasing Student Enrolment in Tourism Programmes at Nigeria’s Universities: Perspectives of the National Open University of Nigeria’s (NOUN) BSc Tourism Studies Programme Administrators - Majebi, Enesi; Omuya, Sefinat; Fagbolu, Olukemi (Faculty of Economics and Business, University of Mataram, 2024)
The BSc tourism studies programme at the National Open University of Nigeria’s (NOUN) major study centres is experiencing instability in student enrolment. This study examined the attracting and retaining strategies being used by 10 key administrators of the NOUN to boost student enrolment in the programme, using a semi-structured interview technique, based Koch et al.’s student enrolment model. The research participants comprised 6 study centre directors (1 from each of the 6 geopolitical zones of Nigeria), the director of the NOUN’s learners support services, the dean of the faculty where the programme is domiciled, and the head of the programme. Results from the transcribed interviews which were content-analysed based on the student enrolment model and emergent themes show that although the NOUN’s stakeholders are making efforts, including visiting public places with flyers to inform prospective students about the programme, more needs to be done, especially by the host department to boost student enrolment in the programme. Consequently, these findings suggest the need for concerted efforts among the NOUN’s stakeholders to adopt and design measures to help identify and address low student enrolment in the programme, including changing its name to e.g., BSc Tourism and Hospitality Management.